2013
DOI: 10.1186/1471-2164-14-769
|View full text |Cite
|
Sign up to set email alerts
|

CEG: a database of essential gene clusters

Abstract: BackgroundEssential genes are indispensable for the survival of living entities. They are the cornerstones of synthetic biology, and are potential candidate targets for antimicrobial and vaccine design.DescriptionHere we describe the Cluster of Essential Genes (CEG) database, which contains clusters of orthologous essential genes. Based on the size of a cluster, users can easily decide whether an essential gene is conserved in multiple bacterial species or is species-specific. It contains the similarity value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…6). We BLASTaligned 458 core eukaryotic genes (Cluster of Essential Genes (CEG) database) 25 to the genome assembly with core eukaryotic genes mapping approach (CEGMA) pipeline 26 , which showed high-confidence hits of 453 (98.8%) and 458 (100%) CEG proteins for all 458 essential genes in CEG with full length (>70% alignment) in the genome of B. juncea and B. nigra, respectively (Supplementary Table 14a). We validated the assembled genomes by matching expressed sequence tags (ESTs) downloaded from the US National Center for Biotechnology Information (NCBI) database, which indicated that 98.9% and 98.2% ESTs were supported by the assembled genomes of B. juncea and B. nigra (>50% alignments), respectively (Supplementary Table 14b).…”
Section: Genome Assembly Scaffold Anchoring and Annotationmentioning
confidence: 99%
“…6). We BLASTaligned 458 core eukaryotic genes (Cluster of Essential Genes (CEG) database) 25 to the genome assembly with core eukaryotic genes mapping approach (CEGMA) pipeline 26 , which showed high-confidence hits of 453 (98.8%) and 458 (100%) CEG proteins for all 458 essential genes in CEG with full length (>70% alignment) in the genome of B. juncea and B. nigra, respectively (Supplementary Table 14a). We validated the assembled genomes by matching expressed sequence tags (ESTs) downloaded from the US National Center for Biotechnology Information (NCBI) database, which indicated that 98.9% and 98.2% ESTs were supported by the assembled genomes of B. juncea and B. nigra (>50% alignments), respectively (Supplementary Table 14b).…”
Section: Genome Assembly Scaffold Anchoring and Annotationmentioning
confidence: 99%
“…In addition, we curated different lists of genes and other genomic elements that were expected to be under negative selection against CNV (see Supplementary information (Tables S2-S5)). These lists included Mendelian disease implication, essentiality 53 , the International Standards for Cytogenomic Arrays (ISCA) dosage sensitivity map 28 , Database of Chromosomal Imbalance and Phenotype in Humans using Ensembl Resources (DECIPHER) 27 , and genomic indices of selective pressure and conservation (see Supplementary information (Table S4)). Significantly higher variability for constrained elements in one study than others was interpreted as a sign of lower specificity (see Supplementary information (Figures S7-S15; Table S6)).…”
Section: Segmental Duplicationsmentioning
confidence: 99%
“…We used all 296 single-copy essential genes of E. coli , which are used as a reference set in Geptop, to test the impact of duplication events on gene essentiality. Similar to the Cluster of Essential Genes database (CEG) ( 29 ), in IFIM, only the gene name is used to identify multiple copy genes. By searching the annotations of Salmonella enterica , we found that the E. coli essential genes ssb , ftsl and trpS had multiple copies in S. enterica serovar Typhi Ty2, and trpS had multiple copies in S. enterica serovar Typhimurium 14028S.…”
Section: Construction and Content Of The Ifim Databasementioning
confidence: 99%